2014
DOI: 10.1155/2014/150319
|View full text |Cite
|
Sign up to set email alerts
|

Firefly Optimization and Mathematical Modeling of a Vehicle Crash Test Based on Single-Mass

Abstract: In this paper mathematical modeling of a vehicle crash test based on a single-mass is studied. The model under consideration consists of a single-mass coupled with a spring and/or a damper. The parameters for the spring and damper are obtained by analyzing the measured acceleration in the center of gravity of the vehicle during a crash. A model with a nonlinear spring and damper is also proposed and the parameters will be optimized with different damper and spring characteristics and optimization algorithms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Different forms are configured and used in analyzing the crash response. For instance, the basic lumped mass model consists of masses and linear springs [1], LPM including beam elements, plastic hinges, nonlinear contact spring elements, and rigid solids [2], and models using nonlinear spring and damper [3,4]. However, considering the mathematical complexity of a crash event representation, it was concluded that the determination of the force elements in the mathematical model has a remarkable influence on response prediction [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Different forms are configured and used in analyzing the crash response. For instance, the basic lumped mass model consists of masses and linear springs [1], LPM including beam elements, plastic hinges, nonlinear contact spring elements, and rigid solids [2], and models using nonlinear spring and damper [3,4]. However, considering the mathematical complexity of a crash event representation, it was concluded that the determination of the force elements in the mathematical model has a remarkable influence on response prediction [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In [7], the authors proposed an approach to control the seat belt restraint system force during a frontal crash to reduce thoracic injury. Klausen et al [8,9] introduced a firefly optimization method to estimate parameters of vehicle crash test based on a single spring-mass-damper model. Ofochebe et al in [10], studied the performance of vehicle front structure using a 5-DOFs lumped mass-spring model composed of body, engine, the cross-member, the suspension and the bumper masses.…”
Section: Introductionmentioning
confidence: 99%
“…), simulate the system. Pawlus et al [7][8][9] fit the real car displacement to the model's responses by applying an LPM, and in Klausen et al, 5 various types of LPM together with a firefly optimization are applied.…”
Section: Introductionmentioning
confidence: 99%
“…There are usually two categories of vehicle crash analysis: finite element method (FEM) models and lumped parameter models (LPM). 5 The analysis by FEM is generally done by making models on CAD software. This method provides a very detailed analysis and gives the material responses during the crash.…”
Section: Introductionmentioning
confidence: 99%